Optimal investment decision-making of energy storage technologies on renewable energy generation side based on the Internal Type-2 trapezoidal fuzzy sets-PROMETHEE-II method - Hui Li; Xilong Yao; Jintao Lu (International Journal of Electrical Power & Energy Systems, 2025)
Energy storage on renewable energy generation side is considered as an effective measure to promote the sustainable development of electric power system. Existing researches have demonstrated the economic and technical feasibility of energy storage. However, how to make the optimal investment decision-making requires further investigation. This paper proposes a more comprehensive investment decision-making indicator system by incorporating resource utilization indicators, such as land use intensity, mineral resource consumption and fossil energy consumption. In addition, this paper constructs an investment decision-making model by integrating the interval type-2 trapezoidal fuzzy sets with PROMETHEE-II method, considering the fuzziness and uncertainty in the investment decision-making process. Finally, this paper analyzes and compares the influence of single objective and multiple objectives portfolio on the investment decision-making. The results show that life cycle sustainability is ranked from highest to lowest as pumped energy storage, hydrogen production by wind power, compressed air energy storage and lithium iron phosphate battery energy storage, with the net flow are 0.872, 0.575, −0.219 and −1.229, respectively. When enterprises consider the economic benefits priority, green development priority and social benefits priority, hydrogen production by wind power is the optimal investment selection. When enterprises consider technology priority and resource conservation priority, pumped energy storage becomes the optimal investment selection. When enterprises consider multiple objectives portfolio, pumped energy storage has been favored by most enterprises. This research can not only promote the large-scale application of energy storage technologies, but also promote the low-carbon development of electric power system.